1991
DOI: 10.1002/jmv.1890330412
|View full text |Cite
|
Sign up to set email alerts
|

Significance of IgM anti‐hepatitis D virus (HDV) in chronic HDV infection

Abstract: Intrahepatic hepatitis D virus (HDV) antigen (HDAg) and serum HDV RNA are excellent markers of active HDV replication but the relation of IgM anti-HDV to HDV replication and histological activity is less certain. To further elucidate the significance of serum IgM anti-HDV, 90 paired sera and liver biopsies from 64 patients seropositive for total antibody to HDV were analysed for IgM anti-HDV, intrahepatic HDAg expression, and histological inflammatory activity. IgM anti-HDV was strongly associated with intrahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…It requires the helper function of hepatitis B virus (HBV) for transmission and replication [2]. Clinically, HDV is usually defined as superinfection in the individuals with viral hepatitis B. HDV infections defined in Europe and in Turkey are usually associated with severe liver damage [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It requires the helper function of hepatitis B virus (HBV) for transmission and replication [2]. Clinically, HDV is usually defined as superinfection in the individuals with viral hepatitis B. HDV infections defined in Europe and in Turkey are usually associated with severe liver damage [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…1 Though the last 2 decades have seen a substantial decline in the circulation of HDV and the incidence of new forms of the disease in southern Europe, 2,3 there is still residual manifestation of the disease in patients infected years ago when HDV was endemic; these patients pose a difficult therapeutic challenge, as most have advanced disease and cirrhosis.…”
mentioning
confidence: 99%
“…20 The role of IgM anti-HDV has been systematically studied in our Institute which showed only a weak correlation between serum IgM anti-HDV and both hepatic HDAg expression and inflammatory activities, indicating that IgM anti-HDV is not a good serum marker for active HDV replication nor active liver disease. 205 A recent study in our Institute showed that serum IgA anti-HAV was almost exclusively associated with chronic HDV infection and was an independent correlate of moderate/severe histological activity with a sensitivity of 82-6% and a specificity of 90.5%. 2027 There was, however, no correlation between serum IgA anti-HDV and expression of hepatic HDAg and serum transaminases.…”
Section: Pathogenesis Of Liver Diseasementioning
confidence: 89%